Illicit love : interracial sex and marriage in the United States and Australia - McGrath, Ann, 1956- (Borderlands and transcultural studies., 2015)
"Illicit Love is a history of love, sex, and marriage between Indigenous peoples and settler citizens at the heart of two settler colonial nations, the United States and Australia. Award-winning historian Ann McGrath illuminates interracial relationships from the late eighteenth to the early twentieth century through stories of romance, courtship, and marriage between Indigenous peoples and colonizers in times of nation formation. The romantic relationships of well-known and ordinary interracial couples provide the backdrop against which McGrath discloses the "marital middle ground" that emerged as a primary threat to European colonial and racial supremacy in the Atlantic and Pacific Worlds from the Age of Revolution to the Progressive Era. These relationships include the controversial courtship between white, Connecticut-born Harriett Gold and southern Cherokee Elias Boudinot; the Australian missionary Ernest Gribble and his efforts to socially segregate the settler and aboriginal population, only to be overcome by his romantic impulses for an aboriginal woman, Jeannie; the irony of Cherokee leader John Ross's marriage to a white woman, Mary Brian Stapler, despite his opposition to interracial marriages in the Cherokee Nation; and the efforts among ordinary people in the imperial borderlands of both the United States and Australia to circumvent laws barring interracial love, sex, and marriage. Illicit Love reveals how marriage itself was used by disparate parties for both empowerment and disempowerment and came to embody the contradictions of imperialism. A tour de force of settler colonial history, McGrath's study demonstrates vividly how interracial relationships between Indigenous and colonizing peoples were more frequent and threatening to nation-states in the Atlantic and Pacific worlds than historians have previously acknowledged"--